2019
DOI: 10.1136/jim-2018-000748
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Hospital Factors associated with 30-Day Unplanned Readmission in Patients with Stroke

Abstract: Stroke is frequently associated with readmission; moreover, readmission is regarded as an important indicator of the quality of stroke care. Thus, we investigated factors associated with 30-day readmission in patients with stroke in South Korea. We used claims data from 2013 for stroke (I60-I62) patients (n=44 729) in 94 hospitals and classified unplanned readmission according to the Centers for Medicare and Medicaid guidelines. We used multilevel models to investigate patient (age, gender, type of insurance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Contributing factors to readmissions include falls, urinary tract infection and recurrence of stroke (Abreu et al, 2020;Kilkenny et al, 2020). These factors are preventable via person-centred discharge planning and follow-up support after discharge (Abreu et al, 2020;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors to readmissions include falls, urinary tract infection and recurrence of stroke (Abreu et al, 2020;Kilkenny et al, 2020). These factors are preventable via person-centred discharge planning and follow-up support after discharge (Abreu et al, 2020;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There was no definite answer in our current analysis. In terms of length of hospital stay, some Korean and American studies (7,12,33,36) suggested that the length of hospital stay affects the 30-day readmission in patients with ischemic stroke, which was corroborated by the results of a few prospective cohort studies (32,38). Conversely, other studies from Norway (4), Australia (35), and China (28) reported opposing results.…”
Section: Discussionmentioning
confidence: 97%
“…Length of hospital stay and age have been explored in many studies, but the type of data reported varied widely across studies. (4,11,30,34,35) reported the medians and quartiles, while Crispo et al and Lee et al (12,36) performed subgroup comparisons. The same was true for age, with means and SD (4,5,7,17,18,22,28,30,34), medians and quartiles (11,35), and subgroup comparisons (12,18,29,33,36) being reported in different articles, which proved problematic in allowing us to obtain accurate quantitative results via meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was reported in Korea and Taiwan respectively [11,18]. On the other hand, 29% were readmitted within 31 days for stroke-related conditions in China [19].…”
Section: Plos Onementioning
confidence: 99%